1993
DOI: 10.1210/jcem.77.3.7690363
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maturational stage on insulin sensitivity during puberty.

Abstract: During puberty, plasma insulin levels increase, and insulin sensitivity decreases along with multiple other physical and hormonal changes. To determine 1) the time course of the decrease in insulin sensitivity in relationship to Tanner stage of genital development, and 2) how this change relates to changes in GH secretion, insulin-like growth factor-I (IGF-I), IGF-binding protein-3, and gonadal steroid secretion, we studied 58 healthy children and adolescents (34 males and 24 females; age 7-15 yr) using overni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
2
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 0 publications
5
84
2
2
Order By: Relevance
“…It is very interesting that IR HOMA , which is a gross index of insulin resistance, showed the same patterns reported with the measure of glucose uptake with an accurate technique like euglycemic clamp. The variation of insulin resistance during puberty in girls may be likely explained by growth hormone=IGF-1 axis changes during puberty (Amiel et al, 1986;Cook et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…It is very interesting that IR HOMA , which is a gross index of insulin resistance, showed the same patterns reported with the measure of glucose uptake with an accurate technique like euglycemic clamp. The variation of insulin resistance during puberty in girls may be likely explained by growth hormone=IGF-1 axis changes during puberty (Amiel et al, 1986;Cook et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Others have also reported that insulin resistance remains elevated throughout puberty. 2,24,39 However, insulin resistance does eventually decrease during adulthood, while the amount of FM and percentage body fat increases, so factors other than FM are probably also involved. Our results that insulin resistance was most related to total adiposity are contrary to adult data that have shown AVF is most strongly linked to insulin resistance in adults.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] In Caucasian children, decreased SI during puberty is accompanied by increased insulin secretion that normalizes as insulin resistance improves near the end of puberty. 5 Cross-sectionally, Moran et al 3 showed that SI (measured using the euglycemic-hyperinsulinemic clamp) was highest in Tanner stage I, lowest in Tanner stage III (B20% lower than stage I), and near prepubertal levels in Tanner stage V. Using a longitudinal design, Goran and Gower 2 observed that the pubertal transition from Tanner stage I to III was associated with a 32% reduction in SI (measured by the intravenous glucose tolerance test and minimal modeling) in Caucasian and African-Americans which was consistent across a range of body fatness.…”
Section: Introductionmentioning
confidence: 99%